Transition Policy of The Changes of The Bone Regional Government in The Pandemic on Public Service - Andi Amytia Resty Dwiyanti (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Singaperbangsa Karawang, 2022)
The Covid-19 that hit Indonesia, especially in the Bone regency, has provided a new order in bureaucracy and changes in work patterns. This condition faced by the government to make changes to the new normal. This study uses qualitative descriptive methods, with library research.The results of this study found that there are two dimensions of government change. Changes in the bureaucratic institutions and the dimensions of the work system. In the dimension of bureaucratic institutional change,over normal disruption occurs, in this caserequires organizations to make to new normal changes. Where the bureaucracy in providing public services, especially at the population and civil registry office of Bone regency, still prioritizes health protocols. Meanwhile in the dimension of work system, there are two choices, working at home and continuing to work in the officeand following the health protocols. In Covid-19, there are many electronic-based public service innovation, so it is necessary to strengthen quality and innovative of human resources.The implications of this research is the success of government change strongly influenced by leadership factors. Leaders who have personality, visionary, and the sense of power are able to face changes or in this case government in Bone Regency. Keywords: Covid 19, Transition Policy, Public Service, Bone Regency